The Analysis of Governance in BUMDes Sumber Rejeki: Integration of Public Sector Governance Aspects and Managerial Functions - Aryanti, Aisyah; Syamsir, Syamsir (The Future of Education Journal, 2025)
The increase in the number of Village-Owned Enterprises (BUMDes) in Indonesia reflects a positive trend in strengthening the rural economy. However, these enterprises still face various challenges related to governance and operational effectiveness. This study aims to analyze the governance of BUMDes Sumber Rejeki in Sari Mulya Village by integrating public sector governance aspects with the managerial functions of public organizations. This research uses a descriptive qualitative method with purposive sampling techniques, data collection through in-depth interviews and document analysis, and data analysis using the Miles and Huberman model. The findings reveal that organizational structure and participatory leadership have been established. However, recruitment mechanisms, procedural documentation, internal supervision, and risk management have not been fully optimized. Managerial functions such as planning, organizing, mobilizing, and controlling have been implemented adaptively, but they are not yet integrated into a sustainable institutional system. These findings suggest that strengthening written Standard Operating Procedures (SOPs), internal evaluation systems, community participation, and local potential-based planning are strategic steps toward building a more accountable and sustainable governance model for BUMDes.